CURRENT ANESTHESIA METHODS FOR NO-SCALPEL VASECTOMY: A SYSTEMATIC REVIEW - Rahman, Fakhri; Birowo, Ponco; Rasyid, Nur (Majalah Kedokteran Indonesia, 2019)
Introduction: This study was aimed to described current anesthesia methods to facilitate no-scalpel vasectomy procedure. Methods: A systematic review based on PRISMA guideline was conducted which included all the studies discussing no-scalpel vasectomy and focusing on its anesthesia method. Outcomes searched were pain during anesthesia and procedure. Literature search was done through search engines (PubMed, EBSCO Host and Cochrane library) using (?no-scalpel vasectomy? OR ?scalpel-free vasectomy? OR ?vasectomy?) AND (?anesthesia?) as keywords and through manual search. Literature selection process was done by two reviewer and qualified studies were subjected to quality assessment. Results: A total of 446 literatures were found and five studies satisfying the eligibility criteria and discussed following anesthesia methods: local infiltration anesthesia (LIA), spinal cord block (SCB), no-needle anesthesia (NNA), mini-needle anesthesia (MNA) and eutectic mixture of local anesthetic (EMLA). This study showed that the average score of pain (VAS 1-10) during no-scalpel vasectomy procedure for LIA, combination of LIA and SCB, NNA, MNA and combination of LIA and EMLA were 1.86 ? 2.7, 0.64, 0.66 ? 2.13, 0.66 and 2.15, respectively. Conclusion: Combination of LIA and SCB, NNA and MNA showed promising results as anesthesia methods. However, these promising results should be further proven by more studies.